A retrospective interventional study for evaluation of efficacy and safety of sildenafil citrate in improving intrauterine growth restriction and oligohydramnios using ultrasound Doppler velocimetry - Ganla, Kedar N.; Choudhary, Rana A.; Desai, Kavita N.; Kadam, Santoshi B.; Arunachalam, Krutika (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Intrauterine growth restriction (IUGR) is one of the major reasons for neonatal morbidity and mortality. Oligohydramnios is a common finding in IUGR. In majority of these cases diminished utero-placental blood flow is observed. However, in spite of this understanding and identification of high-risk patients, the management options are limited. Sildenafil citrate, a phosphodiesterase type-5 inhibitor improves utero-placental perfusion. Methods: We present a retrospective interventional study involving 50 adult pregnant women diagnosed with early-onset IUGR (n=38) and oligohydramnios (n=12). Vaginal sildenafil citrate 25 mg t.i.d. was started from the day of diagnosis till delivery. Primary efficacy endpoints included changes in Doppler parameters i.e., amniotic fluid index (AFI), uterine artery (UA)- pulsatility index (PI), resistance index (RI) and systolic diastolic ratio (S/D ratio). Secondary endpoints included live birth, birth weight, Apgar score at birth, neonatal survival to hospital discharge and adverse maternal side effects. Results: There was a statistically significant improvement in UA-PI, RI and S/D ratios (p<0.0001) in all cases. In oligohydramnios cases, treatment showed a statistical significant increase in AFI score (2.86±1.33 cm). The mean birth weight on delivery was 2200 gm with good Apgar scores. No major adverse effects were reported by women using sildenafil citrate vaginally. Conclusions: Sildenafil citrate, by increasing utero-placental perfusion, improves uterine artery Doppler patterns, AFI, fetal weight and overall better neonatal survival rates by reducing neonatal morbidity and mortality. Sildenafil citrate may hold a promising treatment strategy for management of IUGR and oligohydramnios.